Image Integration to Guide Catheter Ablation in Scar‐Related Ventricular Tachycardia. (5th April 2016) - YAMASHITA, SEIGO; SACHER, FRÉDÉRIC; MAHIDA, SAAGAR; BERTE, BENJAMIN; LIM, HAN S.; KOMATSU, YUKI; AMRAOUI, SANA; DENIS, ARNAUD; DERVAL, NICOLAS; LAURENT, FRANÇOIS; SERMESANT, MAXIME; MONTAUDON, MICHEL; et al.
Image Integration‐Guided VT Ablation: Background: Although multi‐detector computed tomography (MDCT) and cardiac magnetic resonance (CMR) can assess the structural substrate of ventricular tachycardia (VT) in ischemic cardiomyopathy (ICM), non‐ICM (NICM), and arrhythmogenic right ventricular cardiomyopathy (ARVC), the usefulness of systematic image integration during VT ablation remains undetermined. Methods and Results: A total of 116 consecutive patients (67 ICM; 30 NICM; 19 ARVC) underwent VT ablation with image integration (MDCT 91%; CMR 30%; both 22%). Substrate was defined as wall thinning on MDCT and late gadolinium‐enhancement on CMR in ICM/NICM, and as myocardial hypo‐attenuation on MDCT in ARVC. This substrate was compared to mapping and ablation results with the endpoint of complete elimination of local abnormal ventricular activity (LAVA), and the impact of image integration on procedural management was analyzed. Imaging‐derived substrate identified 89% of critical VT isthmuses and 85% of LAVA, and was more efficient in identifying LAVA in ICM and ARVC than in NICM (90% and 90% vs. 72%, P < 0.0001), and when defined from CMR than MDCT (ICM: 92% vs. 88%, P = 0.026, NICM: 88% vs. 72%, P < 0.001). Image integration motivated additional mapping and epicardial access in 57% and 33% of patients. Coronary and phrenic nerve integration modified epicardial ablation strategy in 43% of patients. The impact of image integration on procedural management was higher in ARVC/NICM than in ICM (P < 0.01), and higher in case of epicardial approach (P < 0.0001). Conclusions: Image integration is feasible in large series of patients, provides information on VT substrate, and impacts procedural management, particularly in ARVC/NICM, and in case of epicardial approach.